Government secrecy and the right of the people to know an exploratory study on the breakdown of the free flow of information - Pascual, Alfa Mari Beredo 1978-; Rabanes, Odeon Paul Clemen; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The concept of governance is as old as written history. Many forms of power and authority have evolved in man's pursuit of effective governance, spurring the birth of the ways and means by which control is exercised. Secrecy in the government may have evolved when information control was believed to be expedient in the preservation of the national security of a nation. The practice of government secrecy, however, has a propensity to infringe on the pillars and principles of freedom and democracy. This study on government secrecy is an exploratory study on the breakdown of the free flow of information. The researchers believe that information control and manipulation, consequently inherent in the practice of government secrecy, disrupts the ideal free flow of information. The rationale of the study is to primarily postulate the value of truth and importance of information as the impetus for the pursuit of truth and the protection of truth itself. The study then attempts to explain the intricacies of government secrecy and its tendency to violate the right of the people to know. The significance of the study lies in the proponent's efforts to add to the body of knowledge essential in understanding the world of communication. There were only a handful of useful sources for the related literature composed of the laws and policies, books by foreign authors and articles of some journalists. The researchers developed the Theory of Selective Disclosure based on the three presuppositions agreed upon, complementary to the other assumptions made in the study. The conduct of the study was based upon the verification of the subject and entails verbal admission and presentation of prima facie evidence. Government officials and media practitioners with knowledge on the subject were interviewed to provide for different perspectives. Discussion of the results involved extrapolating from the related literature, the testimonies of the respondents and the examination of the documents. The results of the study verify the existence and practice of government secrecy as a legal mechanism expedient in securing and safeguarding information vital to government functions and processes, specifically in matters of national security. The government enacted laws and formulated policies based on those laws to provide a system of information processes. The media however remains doubtful of its practice in the Philippines even with the passage of laws guaranteeing greater access to information and policies on transparency and full disclosure. The issues arise when there are cases where the government does not provide clear and sufficient information and thereby violate the absolute right of the people to know. The researchers concluded that the assumptions are correct. However, the problems raised cannot be answered by a simple yes or no, or both, in this study. The researchers recommend further studies on other points in this study of national significance.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Government securities -- Philippines